1983
DOI: 10.1113/jphysiol.1983.sp014530
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ouabain on carotid body chemoreceptor activity in the cat.

Abstract: SUMMARY1. The effects of infusions of ouabain on chemoreceptor activity recorded from the peripheral end of a sectioned carotid sinus nerve were studied in cats anaesthetized with pentobarbitone.2. Ouabain caused a marked increase in chemoreceptor discharge followed by a decline in discharge to frequencies near or below the pre-ouabain level; during the latter period further administration of ouabain had no effect.3. Infusion of ouabain during hypoxia further increased the chemoreceptor discharge, but this eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Digoxin increased peripheral chemosensitivity by approximately 50%. This is consistent with previous studies in both animals 17,18 and humans 19 . However, in contrast with results from animals studies, sensitization of the CB did not affect ventilation under normoxic conditions in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Digoxin increased peripheral chemosensitivity by approximately 50%. This is consistent with previous studies in both animals 17,18 and humans 19 . However, in contrast with results from animals studies, sensitization of the CB did not affect ventilation under normoxic conditions in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Digoxin has been part of the therapeutic armamentarium of heart failure for a long time and is currently still recommended for symptomatic patients already receiving optimized standard therapy 16 . Digitalis sensitizes the CB in animals 17,18 and in healthy humans by increasing the ventilatory response to hypoxia, 19 but does not affect sympathetic outflow 19 . Whether this affects exercise tolerance is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Further, patients in these previous studies were not treated with β-blockers or ARBs but were receiving digoxin. Digoxin is no longer the preferred treatment for patients with CHF (Lewis et al, 1989), and has been shown to sensitize the CC (Quest and Gillis, 1971;McQueen and Ribeiro, 1983;Schobel et al, 1994;Janssen et al, 2010). Future clinical trials investigating the effect of CC-mediated CV function before and after treatment may provide further insight into the benefits of pharmacotherapy on CC function.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…At sensory nerve terminals, a sodium pump Sodium pump regulation of cough Canning and Farmer 141 [52,53]. Inhibition of sodium pump function may acutely increase generator potential amplitude and thus terminal excitability [54][55][56]. But with sustained and/or marked inhibition, an accumulation of Na + at the terminals would eventually develop and would impair gating of Na + channels involved in both generator potential formation but also action potentials.…”
Section: Sodium Pump Regulation Of Afferent Neuron Excitability and Ementioning
confidence: 99%